Predicting Delayed Complications After Esophagectomy in the Current Era of Early Discharge and Enhanced Recovery. Issue 6 (June 2020) - Barrie, J.; Cockbain, A.; Tsachiridi, M.; Surendrakumar, V.; Maxwell, M.; Tamhankar, A. P.
Background: Enhanced recovery protocols after esophagectomy aim to discharge patients by day 7. A small risk of delayed complications exists. We aimed to assess whether C-reactive protein (CRP) levels on day 7 could help predict delayed complications and assist safe discharge. Methods: All consecutive esophagectomies over 3 years were retrospectively reviewed. Patients were categorized on day 7 into (1) those clinically unsafe for discharge; (2) those clinically safe for discharge; and (3) those considered safe for discharge but develop a delayed complication. CRP level on day 7 and the trend in CRP levels between days 3 and 7 were compared. Results: A total of 140 patients underwent esophagectomy, of which 64 patients (46%) had at least one complication. On day 7, 62 (44%) patients were considered clinically unsafe for discharge; 74 (53%) were considered safe for discharge; and 4 (3%) were safe but developed a delayed complication. No patient with delayed complication had a day 7 CRP level < 84 mg/L. CRP trend did not help predict delayed complications. Conclusions: The actual CRP level on day 7 after esophagectomy, rather than the trend, can predict delayed complications. Early discharge after esophagectomy should be desisted if the clinical picture is better than the actual blood results.